2017
DOI: 10.1039/c7py01195d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cinnamoyl and coumarin functionalized aliphatic polycarbonates

Abstract: With the objective of generating photo-responsive polymers, carbonate monomers with pendant cinnamoyl or coumarin moieties, which are capable of photo-reversible dimerization, were synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…It is also reported that coumarin photocages can be cleaved via two‐photon processes with near‐infra‐red irradiation . In addition, functionalized aliphatic polycarbonates, photodegradable hydrogels, and drug delivery systems based on coumarin derivatives have been developed. Furthermore, the ability of some coumarin polyesters to undergo chain scission or crosslinking upon certain wavelength irradiation has been demonstrated …”
Section: Methodsmentioning
confidence: 99%
“…It is also reported that coumarin photocages can be cleaved via two‐photon processes with near‐infra‐red irradiation . In addition, functionalized aliphatic polycarbonates, photodegradable hydrogels, and drug delivery systems based on coumarin derivatives have been developed. Furthermore, the ability of some coumarin polyesters to undergo chain scission or crosslinking upon certain wavelength irradiation has been demonstrated …”
Section: Methodsmentioning
confidence: 99%
“…The preparation of coumarin‐ and cinnamoyl‐functionalized polycarbonates has been reported by Amsden and co‐workers. These photoresponsive copolycarbonates are capable of stabilizing polymersomes by cross‐linking under irradiation with 365 nm UV light for 15 min …”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…These photo responsive copolycarbonates are capable of stabilizing polymersomes by crosslinking under irradiation with 365 nm UV light for 15 min. [78,79] Khoee and co-workers developed UV-and pH-dual responsive iminocoumarin-chitosan nanoparticles (CS-COU-NPs) as drug carrier for quercetin, exposing higher stability after photo-crosslinking of 8-formyl-7-hydroxy-4-methyl coumarin (8-FHMC) (Figure 14a). Under physiological condition (pH 7.4), ≈20% quercetin was released from the photocrosslinked nanoparticles, while an accelerated release of 50% quercetin was achieved at pH 5.8 attributing to the acidinduced cleavage of Schiff-base linkage between chitosan and 8-FHMC.…”
Section: Photoinduced Cross-linking/decross-linking Systemsmentioning
confidence: 99%
“…from other stimuli whose control is limited by time and location, drug release triggered by light can be precisely modulated by selecting suitable irradiation parameters regarding light wavelength, intensity, irradiation time, and spatial resolution. [11][12][13] Several light-responsive polymeric systems used as drug carriers have been explored to rapidly release encapsulated payload in exposure to UV light. [14][15][16][17] Recently, a novel o-nitrobenzyl (ONB)functionalized light-responsive aliphatic polycarbonate (LrPC) has been used as drug carrier for photosensitizer 5,10,15,20-tetrakis(m-hydroxyphenyl) chlorin (mTHPC).…”
Section: Doi: 101002/marc201900348mentioning
confidence: 99%
“…Recently, PU nanoparticles with stimuli‐responsive properties, including pH, redox, and temperature sensitivity have been widely investigated as drug carriers. Differing from other stimuli whose control is limited by time and location, drug release triggered by light can be precisely modulated by selecting suitable irradiation parameters regarding light wavelength, intensity, irradiation time, and spatial resolution …”
mentioning
confidence: 99%